Grammatical and semantic losses in Abdel Haleem’s English translation of the Holy Quran - Abdelaal, Noureldin Mohamed (2017)
This study focused on grammatical and semantic losses in the translation of the Holy Quran, which refer to the mismatch between the source text and target text in terms of grammar or vocabulary that affect meaning. It specifically aimed to: 1) identify the grammatical and semantic losses in the translation of three selected Meccan Surahs, and the extent they lead to semantic losses, 2) identify the causes of the identified grammatical losses 3) identify other semantic losses, and 4) identify whether these semantic losses are partial or complete, and 5) determine the causes of such semantic losses. This study is situated within the qualitative interpretive paradigm. Data of the study comprised of Abdel-Haleem’s English translation of three Meccan Surahs, and their three Arabic source text (ST) Surahs. The Surahs included in the study are Al- Ana’am (6) (The Livestock), Al-A’raaf (7) (The Heights), and At-Tur (52) (The Mount). Examples from the selected Surahs were selected purposively to address the research questions. Content analysis of the translation of the identified ayahs in the selected Surahs was done, based on Baker’s typology of non-equivalence and Catford’s translation shifts. The findings of the study revealed various types of grammatical loss in Abdel Haleem’s translation of the three selected Meccan Surahs in the Holy Quran. Loss in translating conjunctions was the most frequent type of loss in the translation. The other common types of loss that were identified in the translation were of tense, syntactic order, loss in emphasis, duality and plurality. In addition, most of the identified grammatical losses found to led to partial semantic losses, and sometimes, to complete semantic losses. Other semantic losses in the translation of the Surahs include losses of the denotative and connotative meanings, overtranslation, loss in rhetorical devices and expressive meanings. These losses were the result of several main causes such as the difference in the grammatical system between the ST and the Target text, semantic complexity, culture and the translator’s failure of selecting appropriate equivalents. This study provides a typology of grammatical and semantic losses in the translation of the Holy Quran. The causes of such losses and how they can be reduced in the future are also suggested. The findings of the study have important implications on future translation of the Holy Quran.